Home‐based microbial solution to boost crop growth in low‐fertility soil - Jiang, Meitong; Delgado‐Baquerizo, Manuel; Yuan, Mengting Maggie; Ding, Jixian; Yergeau, Etienne; Zhou, Jizhong; Crowther, Thomas W.; Liang, Yuting (The New phytologist, 2023)
Summary Soil microbial inoculants are expected to boost crop productivity under climate change and soil degradation. However, the efficiency of native vs commercialized microbial inoculants in soils with different fertility and impacts on resident microbial communities remain unclear. We investigated the differential plant growth responses to native synthetic microbial community (SynCom) and commercial plant growth‐promoting rhizobacteria (PGPR). We quantified the microbial colonization and dynamic of niche structure to emphasize the home‐field advantages for native microbial inoculants. A native SynCom of 21 bacterial strains, originating from three typical agricultural soils, conferred a special advantage in promoting maize growth under low‐fertility conditions. The root : shoot ratio of fresh weight increased by 78–121% with SynCom but only 23–86% with PGPRs. This phenotype correlated with the potential robust colonization of SynCom and positive interactions with the resident community. Niche breadth analysis revealed that SynCom inoculation induced a neutral disturbance to the niche structure. However, even PGPRs failed to colonize the natural soil, they decreased niche breadth and increased niche overlap by 59.2–62.4%, exacerbating competition. These results suggest that the home‐field advantage of native microbes may serve as a basis for engineering crop microbiomes to support food production in widely distributed poor soils.